2018
DOI: 10.1111/1365-2656.12847
|View full text |Cite
|
Sign up to set email alerts
|

Experience during development triggers between‐individual variation in behavioural plasticity

Abstract: Behavioural consistency within and across behaviours (animal personality and behavioural syndrome, respectively) has been vigorously studied in the last decade, leading to the emergence of "animal personality" research. It has been proposed recently that not only mean behaviour (behavioural type), but the environmentally induced behavioural change (behavioural plasticity) might also differ between individuals within populations. While case studies presenting between-individual variation in behavioural plastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 67 publications
4
40
2
1
Order By: Relevance
“…Expressing behavior in an unpredictable way might be an effective antipredator strategy, as predators often rely on predictable patterns in prey locomotion (Briffa, ; Highcock & Carter, ; Richardson, Dickinson, Burman, Pike, & Pike, ). Hence, this pattern is somewhat in line with the predictions of state‐dependent safety principle (Dosmann, Brooks, & Mateo, ; Luttbeg & Sih, ; Sih et al, ), where individuals with low climbing speed suffer higher predation risk while being active and should thus be less predictable (but see Urszán et al, ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Expressing behavior in an unpredictable way might be an effective antipredator strategy, as predators often rely on predictable patterns in prey locomotion (Briffa, ; Highcock & Carter, ; Richardson, Dickinson, Burman, Pike, & Pike, ). Hence, this pattern is somewhat in line with the predictions of state‐dependent safety principle (Dosmann, Brooks, & Mateo, ; Luttbeg & Sih, ; Sih et al, ), where individuals with low climbing speed suffer higher predation risk while being active and should thus be less predictable (but see Urszán et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…Although “animal personality research” is one of the fastest developing fields of behavioral ecology, studies on the evolutionary importance of within‐individual behavioral variability started to accumulate only recently (Araya‐Ajoy & Dingemanse, ; Dingemanse, Kazem, Réale, & Wright, ; Stamps, Briffa, & Biro, ). Several studies demonstrated lately that components of within‐individual variation, known as behavioral plasticity (behavioral response induced by environmental change) and behavioral predictability (behavioral variation independent from environmental change), are not only integrated into an individual's behavioral strategy (Chang, Teo, Norma‐Rashid, & Li, ; Lichtenstein, Chism, Kamath, & Pruitt, ; Urszán et al, ; Velasque & Briffa, ), but individual‐specific variation in these components exists (Biro & Adriaenssens, ; Briffa, ; Briffa, Bridger, & Biro, ; Ioannou & Dall, ; Westneat, Wright, & Dingemanse, ). Thus, plasticity and predictability of individual behavior are potentially independent traits, which may be targeted by selection directly (Brembs, ; Mathot & Dingemanse, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…animal personality and behavioural syndromes) on/off in adult animals. Further, it is also known that ontogenetic experience with relevant ecological stimuli is needed for the development of between‐individual variation in mean behaviour and behavioural plasticity (Urszán, Garamszegi, et al., ; Urszán et al., ; Urszán, Török, Hettyey, Garamszegi, & Herczeg, ). Based on the observed flexibility of behavioural consistency within populations, we expected to see some variation in the strength of animal personality and presence/absence of between‐individual variation in behavioural plasticity between sexes and/or brain lines.…”
Section: Discussionmentioning
confidence: 99%
“…Tollrian & Harvell, 1999). However, the fact that the strength of behavioural plasticity varies between individuals; for instance, individuals in a population differ in how much shier they become under perceived predation risk, has only became realized lately both in theoretical (Dingemanse et al, 2010;Dingemanse & Wolf, 2013; and empirical studies (Briffa et al, 2013;Dingemanse, Barber, et al, 2012;Dingemanse, Bouwman, et al, 2012;Porlier et al, 2012;Quinn et al, 2012;Urszán et al, 2018;Westneat et al, 2011). Since it has been shown that between-individual differences in behavioural plasticity can be consistent across individuals, or in other words, can be reliable individual traits (Araya-Ajoj & Dingemanse, 2017;Mitchell & Biro, 2017), the question why such individual differences exist emerged.…”
Section: Discussionmentioning
confidence: 99%